ANAK PEREMPUAN DALAM PERKAWINAN USIA ANAK - Diana Wahyu Rachmawati; Siany Indria Liestyasari; Okta Hadi Nurcahyono (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2021)
This study aims to determine the motives of women doing child marriage. This research was conducted in Saradan Village, Baturetno District, Wonogiri Regency. This study uses qualitative research with a phenomenological approach. Data collection comes from interviews, documentation, and observation. The primary interviews were conducted by women who had child marriages. The data collection technique used is purposive sampling. The data validity testing technique used is source triangulation. The results of the study show as follows: the motives of women marrying at the age of children can be divided into two, namely because of reasons and by motives. Because the motives are 1) Lack of parental attention and supervision, 2) The economic situation of the low-income family, 3) The psychological condition of teenagers, and 4) Low education. While To Motive is 1) Having a better economic life, 2) Having a happy family life, 3) Getting a person who can give attention, affection and responsibility to his life.